Training Organization Features for Foreign Residents According to the Educational Model ‘The Russian Language - Scientific Speech - MedicTest’ - DINEVICH, IRINA A. (The journal of contemporary issues in business and government, 2021)
The article is devoted to the issue of organizing training for foreign residents according to the educational model named ‘The Russian language – Scientific speech – MedicTest’. The article analyzes modern approaches to the methods of teaching the Russian language and the scientific style of speech, characterizes the methodological principles that form the basis of professional communication. The author describes the ways of expressing scientific thought using various typical models of the scientific style of speech, considers the features of the development of productive and receptive grammatical skills used in speech activity, and gives examples of lexico-grammatical tasks. The author focuses particular attention on the specifics of educational work on the study of MedicTest, necessary for admission to residency. Within the framework of this work, great importance is attached to the explanation of medical terminology in Russian, the ability of medical terms to enter into various paradigmatic and syntagmatic relations in the Russian language and to form synonymic terms, terms-antonyms and homonymic terms, are characterized, the features of the formation and use of active and passive constructions in medical texts.